Dot. - Zuckerberg, Randi (Harper, an imprint of HarperCollinsPublishers, 2013)
Dot's a spunky little girl well versed in electronic devices. Dot knows a lot. She knows how to tap... to swipe... to share... and she pays little attention to anything else, until one day Dot sets off on an interactive adventure with the world surrounding her. Dot's tech-savvy expertise, mingled with her resourceful imagination, proves Dot really does know lots and lots.